2017
DOI: 10.1021/acsami.7b06403
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble 2D Transition Metal Dichalcogenides as the Hole-Transport Layer for Highly Efficient and Stable p–i–n Perovskite Solar Cells

Abstract: As a hole-transport layer (HTL) material, poly(3,4-ethylenedioxythiophene):polystyrene-sulfonate (PEDOT:PSS) was often criticized for its intrinsic acidity and hygroscopic effect that would in the long run affect the stability of perovskite solar cells (Pero-SCs). As alternatives, herein water-soluble two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS and WS were used as HTLs in p-i-n Pero-SCs. It was found that the content of 1T phase in 2D TMDs HTLs is centrally important to the power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 57 publications
3
101
0
Order By: Relevance
“…A different approach can involve using lithium intercalation and exfoliation method, as reported by Li and co-workers. 87 The resulting MoS 2 and WS 2 films were used in perovskite solar cells and showed superior performance when compared to PEDOT:PSS-based devices. When stored in ambient conditions, the PCE of the PEDOT:PSS containing device almost degraded completely after 35 days but devices containing MoS 2 and WS 2 showed 78% and 72% of their average PCEs, respectively, after 56 days, highlighting the greater stability that can be achieved by using transition metal dichalcogenide layers.…”
Section: Solution-processed Graphene Oxide and Transition Metal Dichamentioning
confidence: 99%
“…A different approach can involve using lithium intercalation and exfoliation method, as reported by Li and co-workers. 87 The resulting MoS 2 and WS 2 films were used in perovskite solar cells and showed superior performance when compared to PEDOT:PSS-based devices. When stored in ambient conditions, the PCE of the PEDOT:PSS containing device almost degraded completely after 35 days but devices containing MoS 2 and WS 2 showed 78% and 72% of their average PCEs, respectively, after 56 days, highlighting the greater stability that can be achieved by using transition metal dichalcogenide layers.…”
Section: Solution-processed Graphene Oxide and Transition Metal Dichamentioning
confidence: 99%
“…A thin MoO x layer can prevent photobleaching of the MAPbI 3 film and mitigates decomposition. Two water‐soluble two dimensional transition metal dichalcogenide, MoS 2 and WS 2 are used as HTM in PSCs in a study by Huang et al The highest PCEs of 14.35 and 15.00% were obtained for the PSCs with MoS 2 and WS 2 , respectively. In a very recent study, Qin et al have achieved high PCE of 17.19% on glass and 15.53% on flexible PET substrates, introducing and employing a novel copper‐chromium binary metal oxide as HTM for PSCs .…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…Nonetheless, MoS 2 is a good example of versatility these 2D chalcogenides offer, since it can govern both electron and hole transport, either as an interlayer or a dopant. In both cases, significant improvement of device stability and energy alignment with adjacent layers were reported for both inverted and normal perovskite solar cells [35,36]. Kakavelakis et al demonstrated potential of MoS 2 to improve operational stability of inverted perovskite solar cells by suppressing light-induced decline of photocurrent [37].…”
Section: D Materials and Engineering Of Interfacesmentioning
confidence: 99%